Enhancement of Okra (Abelmoschus esculentus L.) Germination through Seed Priming Techniques - Balchhaudi, Anil (Indonesian Journal of Agricultural Research, 2023)
The presence of a hard seed coat, coupled with various abiotic stresses during germination, can result in delayed and erratic crop establishment of okra (Abelmoschus esculentus L.). Seed priming offers an efficient and cost-effective method to improve the emergence of okra seeds. A laboratory experiment was conducted to assess the effect of various priming methods on germination parameters. The investigation was laid out in a Complete Randomized Design (CRD) with six levels of seed priming methods viz. priming with 200 ppm GA3 solution, priming with 80% H2SO4 solution, priming with 0.3% KNO3 solution, priming with 5% PEG-6000 solution, priming with tap water, and control (without priming). The experiment was replicated four times. The effect of various priming methods on physiological and biometric parameters, i.e., germination percentage, mean days to germination, seed vigor index, root length, and shoot length, was investigated. The research results revealed that seed priming methods significantly influenced all the recorded parameters. Priming with GA3 recorded a significantly higher germination percentage (73.75%), root length (114.5 mm), shoot length (85 mm), and seed vigor index (14719 mm). Furthermore, priming with GA3 took significantly fewer mean days to germinate, requiring a mere 5.42 days. Priming with H2SO4 was as effective as priming with GA3 in terms of germination percentage, mean days to germination, seed vigor index, root length, and shoot length. The study concluded that priming with GA3 and priming with H2SO4 can be an effective method to expedite seed germination, enhance germination percentage, and increase the seed vigour of okra. In the absence of GA3 and H2SO4, hydropriming can be a felicitous alternative to combat poor crop emergence in an eco-friendly and cost-effective manner.